2013
DOI: 10.1104/pp.112.211441
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq of Arabidopsis Pollen Uncovers Novel Transcription and Alternative Splicing      

Abstract: (S.M., P.Q.)Pollen grains of Arabidopsis (Arabidopsis thaliana) contain two haploid sperm cells enclosed in a haploid vegetative cell. Upon germination, the vegetative cell extrudes a pollen tube that carries the sperm to an ovule for fertilization. Knowing the identity, relative abundance, and splicing patterns of pollen transcripts will improve our understanding of pollen and allow investigation of tissue-specific splicing in plants. Most Arabidopsis pollen transcriptome studies have used the ATH1 microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
227
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(239 citation statements)
references
References 38 publications
7
227
0
1
Order By: Relevance
“…Gene transcription in mature pollen grains was compared with that in seedling tissues (Loraine et al, 2013). Plotting the mean reads per kilobase per million reads values for the entire set, quantile 1 (lowest transcribed), and quantile 4 (highest transcribed) of all genes, retrogenes, and parents confirmed the microarray data ( Figures 3A, 3E, and 3F; Supplemental Figure 3B).…”
Section: Arabidopsis Retrogenes Are Transcribed In Male Gametesmentioning
confidence: 60%
See 3 more Smart Citations
“…Gene transcription in mature pollen grains was compared with that in seedling tissues (Loraine et al, 2013). Plotting the mean reads per kilobase per million reads values for the entire set, quantile 1 (lowest transcribed), and quantile 4 (highest transcribed) of all genes, retrogenes, and parents confirmed the microarray data ( Figures 3A, 3E, and 3F; Supplemental Figure 3B).…”
Section: Arabidopsis Retrogenes Are Transcribed In Male Gametesmentioning
confidence: 60%
“…Therefore, somatic retroposition events in the shoot apical meristems may also be transmitted to the next generations. Thus, we tested for tissuespecific transcription of retrogenes in Arabidopsis using a developmental transcription data series (Schmid et al, 2005) and validated these findings using RNA sequencing data sets (Loraine et al, 2013). Surprisingly, this revealed that retrogenes are overtranscribed in pollen while overall transcription was not increased at this stage.…”
Section: Retrogenes Are Preferentially Upregulated In Pollenmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Arabidopsis pollen RNA-seq data sets have also shown that in addition to LBD10 and LBD27, the mRNAs from other LBDs including LBD22, LBD25, and LBD36, were significantly detected in pollen. 26 Heterodimerization between 2 different transcription factors facilitates nuclear localization and contributes to transcriptional regulation by modulating DNA-binding specificity and affinity and/ or the recruitment of different binding partners. 27 Thus the protein-protein interactions among these LBD transcription factors may provide redundancy as well as diversity to their biological functions during pollen developmental process.…”
mentioning
confidence: 99%